ANALISIS DETERMINAN KEMISKINAN DI KABUPATEN MIMIKA - Abu Bakar (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2019)
This study aims to analyze the significance of the partial Human Development Index (HDI) and Gross Regional Domestic Product (GRDP) on poverty levels in Mimika Regency, and to analyze the significance of the effect of HDI and GRDP simultaneously on poverty levels in Mimika Regency. The data used in this study are secondary data obtained from BPS Mimika Regency through documentation techniques. To analyze data, multiple linear regression analysis was used. The results showed that: (a) HDI had a negative and significant effect on the level of poverty in Mimika Regency; (b) GRDP has a negative and not significant effect on the level of poverty in Mimika Regency; (c) HDI and GRDP simultaneously have a significant effect on the level of poverty in Mimika Regency.